Total synthesis of cytotoxic sponge alkaloids hachijodines F and G - Goundry, W; Lee, V; Baldwin, J (2002)
The total synthesis of two cytotoxic sponge alkaloids hachijodines F (1) and G (2) via a common intermediate 3 is described. © 2002 Elsevier Science Ltd. All rights reserved.